STRATEGI DINAS SOSIAL, TENAGA KERJA DAN TRANSMIGRASI DALAM MENGURANGI JUMLAH PENGANGGURAN DI KABUPATEN SIAK - Piona, Iir; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study will analyze how the Strategy of Social Service, Manpower and Transmigration in Reducing Unemployment in Siak. Given the number of unemployed either from within or from the outside of the area to look for jobs in Siak government attempted to reduce unemployment by holding job fairs exhibitions in order to facilitate job seekers procure the job.Steps Strategy of Social Service, Manpower and Transmigration in Reducing Unemployment in Siak become very important in providing counseling or dissemination to the public or the unemployed to fill job vacancies that exist both within and outside the region. Then, Social Services, Manpower and Transmigration in Siak also perform or carry out training of workers according to labor market demand according to the expertise or skills possessed by job seekers. The purpose of this study is to determine the strategy of Social Service, Manpower and Transmigration in in Siak and to determine the factors that influence the strategy of Social Service, Manpower and Transmigration in Reducing Unemployment in Siak. For this problem analyze author uses the theory Tripomo, Tejo, and Udan which an analysis of strategies focus on factors that SWOT Strengths, Weaknesses, Opportunities, Threats.This research was conducted in the Department of Social Welfare, Labour and Transmigration in Siak, using qualitative research methods using snowball sampling method in the analyze of research with key informants (keyinforman). In collecting the data, research using interview techniques, observation and communication studies. By using key informants and informant as a supplementary source of information reducing Unemployment in Siak not running with a maximum in carrying out efforts to reduce unemployment. The factors that influence among other factors of infrastructure, human resources, and communications.Keywords: Strategy, Unemployment, Strengths, Weaknesses, Opportunities, Threat.